Generation of barcoded plasmid libraries for massively parallel analysis of chromatin position effects - M. O. Lebedev; L. A. Yarinich; A. V. Ivankin; A. V. Pindyurin (Вавиловский журнал генетики и селекции)
The discovery of the position effect variegation phenomenon and the subsequent comprehensive analysis of its molecular mechanisms led to understanding that the local chromatin composition has a dramatic effect on gene activity. To study this effect in a high-throughput mode and at the genome-wide level, the Thousands of Reporters Integrated in Parallel (TRIP) approach based on the usage of barcoded reporter gene constructs was recently developed. Here we describe the construction and quality checks of high-diversity barcoded plasmid libraries supposed to be used for high-throughput analysis of chromatin position effects in Drosophila cells. First, we highlight the critical parameters that should be considered in the generation of barcoded plasmid libraries and introduce a simple method to assess the diversity of random sequences (barcodes) of synthetic oligonucleotides using PCR amplification followed by Sanger sequencing. Second, we compare the conventional restriction-ligation method with the Gibson assembly approach for cloning barcodes into the same plasmid vector. Third, we provide optimized parameters for the construction of barcoded plasmid libraries, such as the vector : insert ratio in the Gibson assembly reaction and the voltage used for electroporation of bacterial cells with ligation products. We also compare different approaches to check the quality of barcoded plasmid libraries. Finally, we briefly describe alternative approaches that can be used for the generation of such libraries. Importantly, all improvements and modifications of the techniques described here can be applied to a wide range of experiments involving barcoded plasmid libraries.